KETERKAITAN STATUS HARA N, P, K TANAH DENGAN PRODUKSI DAN MUTU TEMBAKAU VARIETAS KEMLOKO DI KABUPATEN TEMANGGUNG, JAWA TENGAH - Radhini Kartika Putri; S Sudarto; D Djajadi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
One of the tobacco producing centers in Indonesia is Temanggung District, Central Java. Varieties that are commonly grown in Temanggung Regency is Kemloko varieties that produce the best quality (srinthil) with high nicotine and used as raw material for making kretek cigarettes. This study was aimed to analys the relevance of nutrient status of N, P, K in soil on production and quality index in Temanggung, and arranging distribution map of N, P, K in Temanggung. The study was conducted by field survey. Results showed that there was no significant correlation between N, P, K on productivity and quality of tobaccoÂ Kemloko varieties in Temanggung regency, Central Java. N, P, K correlation value to productivity that -0.1125, 0.2247, -0.1856. N, P, K correlation to quality index -0.0002, 0.2354, 0.0836. There was no significant correlation between N, P, K with productivity and tobacco quality index on 2016 planted seasonÂ due to high rainfall occurring throughout 2016. Distribution of N-totalÂ in tobacco producing centers in Temanggung was low (0.14%), to moderate (0.35%), P-distriburtion is very high (23.15 ppm P-50.88 ppm P) and K distribution was average (0.48 me 100 g-1) to very high (1.57 me 100 g-1).